Service and dependency in Shakespeare's plays - Weil, Judith (Cambridge University Press, 2005)
This is an unusual study of the nature of service and other types of dependency and patronage in Shakespeare's drama. Attentive to a range of historical sources and cultural issues, Weil also emphasizes the linguistic ambiguities created by service relationships and their rich potential for interpretation on the stage.